2021
DOI: 10.3390/ijerph18084367
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of the Lockdown Due to the COVID-19 Pandemic in University Workers: Factors Related to Stress, Anxiety, and Depression

Abstract: This study aims to explore the psychological impact of the coronavirus disease (COVID-19)-related lockdown in university workers, and to analyse the factors related to their levels of stress, anxiety, and depression. A cross-sectional study was conducted between 8–22 April 2020, 3.5 weeks after the COVID-19-related lockdown in Spain. We collected sociodemographic and occupational data, in addition to housing, work and health conditions. Coping strategies (Brief COPE-28); level of anxiety, stress, and depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 50 publications
4
23
0
1
Order By: Relevance
“…Our founding indicated that female was significantly associated with higher levels of depression, anxiety and stress, which is in accordance with the findings of many other studies around the world. 15 , 16 , 17 , 19 , 20 , 24 , 25 , 26 , 27 However, it should be noted that females were also susceptible to higher levels of depression even before the pandemic. 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our founding indicated that female was significantly associated with higher levels of depression, anxiety and stress, which is in accordance with the findings of many other studies around the world. 15 , 16 , 17 , 19 , 20 , 24 , 25 , 26 , 27 However, it should be noted that females were also susceptible to higher levels of depression even before the pandemic. 37 …”
Section: Discussionmentioning
confidence: 99%
“… 9 , 14 , 15 , 16 , 17 , 18 , 19 Additionally, these studies have also examined factors associated with mental illnesses in COVID-19 patients. Limited access to health care, having pre-existing comorbidities, general health, 15 , 16 , 17 , 18 employment and economic status, 19 , 20 , 21 marital status, 15 , 16 , 22 being female, 15 , 16 , 17 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 and education 20 , 28 , 29 have been identified as associated factors of depression, anxiety and stress in COVID-19 patients in general population.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that a lack of club membership also reflects a lower socioeconomic status, which in turn negatively affects self-reported health [46]. In line, during the COVID-19 outbreak it was found that university workers living in smaller homes reported higher levels of anxiety-depression-and stress symptoms [47]. Also, for college students during the COVID-19 outbreak, economic disadvantage was associated with higher stress levels [48].…”
Section: Discussionmentioning
confidence: 99%
“…Past research shows that psychological distress experienced in the work context may be negatively related to well-being and quality of life and these findings have been observed in a variety of work activities during and after the COVID-19 pandemic, such as health caregivers ( Lenzo et al, 2021 ), undergraduate students ( Mishra et al, 2021 ), and teaching and administration personnel ( Salazar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%